1992
DOI: 10.1111/j.1600-051x.1992.tb00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐surgical periodontal treatment: where are the limits?

Abstract: In the present scanning electron microscopic study, the possibilities and limitations of non-surgical root planing were investigated. 10 single-rooted teeth from 4 patients with advanced periodontitis were studied. The root surfaces were cleaned and planed without flap reflection, using fine curettes. The teeth were then extracted and the root surfaces were systematically examined by scanning electron microscopy (SEM) for the presence of residual bacteria and calculus. 29 of 40 curetted root surfaces were free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 19 publications
0
66
0
5
Order By: Relevance
“…Rateitschak-Plüss et al 39,40 report complete instrumentation achieved on 75% of the root surfaces after non-surgical therapy without differentiation between concrement removal and enhanced root planing as two different steps. It is acknowledged that mechanical therapy alone, especially root planing, has an antiinfective influence.…”
Section: Discussionmentioning
confidence: 98%
“…Rateitschak-Plüss et al 39,40 report complete instrumentation achieved on 75% of the root surfaces after non-surgical therapy without differentiation between concrement removal and enhanced root planing as two different steps. It is acknowledged that mechanical therapy alone, especially root planing, has an antiinfective influence.…”
Section: Discussionmentioning
confidence: 98%
“…Par ailleurs, Marshall [13] a montré que l'augmentation du nombre de caries dentaires est associée à un retard de croissance chez les enfants. La mauvaise hygiène bucco-dentaire est due à une accumulation de la plaque bactérienne qui n'est pas éliminée par un brossage dentaire adéquat [10,11] : elle est donc due à la négligence et/ ou à l'ignorance des parents qui ont tendance à penser que les dents lactéales n'exigent pas une hygiène particulière. Une forte proportion des enfants malnutris (90 %) présentait une mauvaise hygiène bucco-dentaire et une gingivite sévère et généralisée (Tableau III) ; la différence était significative (P = 10 -8 ).…”
Section: Discussionunclassified
“…It has been shown that scaling and root planing is an effective mechanical approach for reducing bacterial colonization to sub-threshold values and also for controlling the progression of periodontal disease. However, thorough subgingival scaling and root planing is technically demanding, as access to and visibility of the area are required, so that complete subgingival plaque and calculus removal is rarely achieved and sometimes ineffective (6), and may not eradicate species that can reach epithelial cells and subepithelial connective tissues of the periodontium (7).…”
Section: Introductionmentioning
confidence: 99%